Женский день: [роман] / Мария Метлицкая - Метлицкая Мария (За чужими окнами, 2015)
Экземпляры: ф.10 (20151012) / Инвентарный номер: 56621 / Цена: / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: М 54 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44